A Cross‐sectional population‐based investigation into behavioral change in amyotrophic lateral sclerosis: subphenotypes, staging, cognitive predictors, and survival. Issue 5 (11th April 2017) - Burke, Tom; Pinto‐Grau, Marta; Lonergan, Katie; Bede, Peter; O'Sullivan, Meabhdh; Heverin, Mark; Vajda, Alice; McLaughlin, Russell L.; Pender, Niall; Hardiman, Orla
Abstract: Objective: Amyotrophic Lateral Sclerosis (ALS) is a clinically heterogeneous neurodegenerative disorder associated with cognitive and behavioral impairment. The primary aim of this study was to identify behavioral subphenotypes in ALS using a custom designed behavioral assessment tool (Beaumont Behavioural Inventory, BBI). Secondary aims were to (1) investigate the predictive nature of cognitive assessment on behavioral change, (2) report the behavioral profile associated with the C9 orf 72 expansion, (3) categorize behavioral change through disease staging, and (4) to investigate the relationship between cross‐sectional behavioral classification and survival. Methods: A cross‐sectional population‐based research design was applied to examine behavioral data from ALS patients ( n  = 317) and healthy controls ( n  = 66). Patients were screened for the C9orf72 repeat expansion. A subcohort of ALS patients completed an extensive cognitive assessment battery ( n  = 65), to investigate predictors of behavior change. Principal component analysis (PCA) determined factors associated with altered behavior. Survival data were extracted from the Irish ALS register. Results: No behavioral changes were reported in 180 patients (57%); 95 patients had mild‐moderate behavioral change (30%); 42 patients met the cut‐off for Clinically Severe Behavioral Change (13%), suggestive of a bvFTD diagnosis. The most frequently endorsed behaviors in ALS were reduced concern for hygiene (36.8%), irritability (36.2%), new unusual habits (33.4%), and increased apathy (31.1%). Five independent factors were identified through factor analysis. Social cognitive performance was predictive of behavior change ( P  = 0.031), yielding an R 2  = 0.188. Behavioral categorization (mild/moderate/severe) at the time of assessment was not associated with survival ( P  = 0.198). Interpretation: These data imply the presence of distinct subphenotypes of behavioral change in ALS, which most likely reflect subcategories of extramotor network disruption.